THE ANALYSIS OF VERBAL COLLACATIONS IN ENGLISH AND UZBEK LANGUAGES - Tillayeva Oltinoy Baxtiyorovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This analysis aims to explore and compare the verbal collocations in English and Uzbek, focusing on how these expressions are formed, the types of verbs commonly  used,  and  the  similarities  and  differences  between  the  two  languages. Understanding these patterns is crucial for learners and translators alike, as it not only aids in language acquisition but also helps in capturing the subtleties of meaning and expression in cross-cultural communication.